Rheumatic heart disease burden and determinants in cardiac patients: A follow up care concern in Ethiopia - Hiwot Berhanu; Elsah Tegene; Morankar Sudhakar; Tadesse Dukessa Gemechu; Andualem Mossie (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Rheumatic heart disease (RHD) is a neglected tropical disease and remains one of the leading causes of cardiovascular-related deaths in Ethiopia. This study aims to assess the burden of RHD and identify its determinants in the country. A hospital-based cross-sectional study was employed from January 5 to April 15, 2023, among cardiac patients attending Jimma Medical Center. Socio-demographic data were collected using a structured interviewer-administered questionnaire and echocardiographic patterns were taken by senior cardiologists. Data were entered into Epidata Version 4.6 and exported to SPSS version 25.0 for analysis. Bivariable and multivariable logistic regressions were performed. A p value < 0.05 was considered statistically significant. Accordingly, the most frequent morbidities were RHD (n = 95, 27.9 %), hypertensive heart disease (n = 92, 27.1 %), ischemic heart disease (n = 54, 15.9 %), and dilated cardiomyopathies (n = 54, 15.9 %). Further, female sex [AOR = 3.06: 95 % CI 1.73–5.47], using wood (biomass fuel) for cooking [AOR = 1.94: 95 % CI 1.10–3.42], history of malnutrition with follow-up at a health facility [AOR = 3.90: 95 % CI 2.22–6.86], dental caries [AOR = 2.09: 95 % CI 1.12–3.87], and living in crowded households [AOR = 2.02: 95 % CI 1.15–3.52] were identified as the determinants of RHD. This finding suggests that focusing on female healthcare, reducing biomass fuel exposure, improving nutritional status, providing regular dental care, and improving living conditions could help reduce the impacts of the disease. Moreover, conducting further research regularly will also benefit the community at large.